Market entry strategies to emerging markets: a conceptual model of turnkey project development - Vassileva, Bistra; Nikolov, Miroslav (Serbian Journal of Management, 2016)
The main purpose of the paper is to analyse the international market entry strategies in the light of globalisation processes and to propose a conceptual model of turnkey projects as market entry mode. The specific research objectives are as follows: 1. to develop an integrated framework of the turnkey marketing process as a conceptual model; 2. to analyse BRICS countries as potential host countries for turnkey projects implementation; 3. to assess potential implications of proposed conceptual model for global market entry decisions.